The Role of Sharia Principles in Promoting Sustainable Economic Development: A Comparative Analysis of Islamic and Non-Islamic Economies - Muhammed Midlaj P (Penerbit Hellow Pustaka, 2024)
This study explores the role of Sharia principles in promoting sustainable economic development, focusing on comparative analysis between Islamic and non-Islamic economies. Sharia, the legal and ethical code of Islam, emphasizes principles such as social justice, equitable distribution of wealth, and ethical investment that are increasingly relevant in discussions of sustainable development. Research examines how these principles contribute to long-term financial stability, environmental protection, and social welfare in Islamic economies. Through detailed analysis of economic indicators and case studies, this study highlights the potential of Sharia-compliant financial practices to promote sustainable development, particularly resource management, poverty alleviation, and ethical business practices. The findings suggest that while Islamic economies have some advantages due to their adherence to Shariah principles, non-Islamic economies could benefit from integrating similar ethical standards into their economic frameworks. This comparative analysis provides insights into how economies around the world can improve their sustainability efforts by adopting and adapting Shariah-inspired principles, contributing to a more equitable and sustainable global economy. The study concludes with policy recommendations for Islamic and non-Islamic countries to incorporate these principles into their economic planning and development strategies.